PENGARUH PENGGUNAAN TEKNIK PRE-READING PLAN DALAM PEMBELAJARAN IPS TERHADAP HASIL BELAJAR SISWA KELAS VIII DI SMPN 2 SUMBER KECAMATAN SUMBER KABUPATEN CIREBON - Maulida Zulfah (SOCIAL PEDAGOGY: Journal of Social Science Education, 2022)
The purpose of this study was to determine: (1) the use of the Pre-reading Plan technique in social studies learning (2) the effect of class VIII student learning outcomes at SMP Negeri 2 Sumber Cirebon (3) how much influence the use of the Pre-reading Plan technique in social studies learning had. on the learning outcomes of class VIII students at SMP Negeri 2 Sumber. In this study, the population and sample were students of SMP Negeri 2 Sumber, class VIII B, amounting to 37 students and class VIII C totaling 37 students. According to the methodology, this type of research is quantitative. Data analysis using the "t" test formula for two large samples that are interconnected with each other, presenting data in the form of group data. Based on the analysis of the "t" test from the results of the study, it shows that to is equal to (3.12) is much greater than t, both at the 5% level (2.03) and 1% at (2.72), namely 2.03 <3 ,12>2.72. Thus, Ho is rejected and Ha is accepted. It means that between variables X and Y there is a significant effect. Based on the results of this study, it can be concluded that there is a significant influence between the Pre-reading Plan technique in social studies learning on the learning outcomes of class VIII students at SMP Negeri 2 Sumber.